2015
DOI: 10.1182/blood-2014-11-608539
|View full text |Cite
|
Sign up to set email alerts
|

Generation of human memory stem T cells after haploidentical T-replete hematopoietic stem cell transplantation

Abstract: Key Points• T SCM lymphocytes are preferentially generated from naive precursors in vivo early after haploidentical HSCT.• T SCM represent relevant novel players in the diversification of immunological memory after haploidentical HSCT.Memory stem T cells (T SCM ) have been proposed as key determinants of immunologic memory. However, their exact contribution to a mounting immune response, as well as the mechanisms and timing of their in vivo generation, are poorly understood. We longitudinally tracked T SCM dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 43 publications
8
129
0
Order By: Relevance
“…14,15 The patient was able to overcome CMV ( Figure 6A) reactivation. Based on his good clinical condition (no sign or symptoms of CMV disease), and because we observed a spike in the CMV-specific CD8 1 host T lymphocyte count, no further antiviral treatment was used.…”
Section: Transplantation Of Haploidentical Megadose Tcd Hsct In High-mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The patient was able to overcome CMV ( Figure 6A) reactivation. Based on his good clinical condition (no sign or symptoms of CMV disease), and because we observed a spike in the CMV-specific CD8 1 host T lymphocyte count, no further antiviral treatment was used.…”
Section: Transplantation Of Haploidentical Megadose Tcd Hsct In High-mentioning
confidence: 99%
“…14,15 Furthermore, our ability to avoid the use of immune-suppressive drugs after Cy administration might help control relapse through the activity of the host and donor T cells, as well as the substantial level of NK cells. Clearly, while no statement regarding relapse can be made based on our limited data, if these patients or future patients treated by this protocol do relapse, they would remain eligible for further treatment with immune cells from the original donor, including chimeric antigen receptor T cells, NK cells, or simply donor lymphocyte infusion.…”
Section: Cd95mentioning
confidence: 99%
“…Simultaneously, T memory stem cells can give rise to more differentiated central memory T cells (T CM cells), effector memory T cells (T EM cells), and terminally differentiated effector memory T cells (T TDEM cells) through transitional proliferation and effectively reconstitute cellular immunity in immunocompromised hosts during serial transplantation experiments in animal models (23). A recent study also showed that T SCM cells are able to persist and to preserve their precursor potential for up to 12 years after lymphocyte infusion in immunodeficient patients (24) and play important roles for regenerating the memory T cell pool after hematopoietic stem cell transplantation (25,26). So far, T memory stem cells recognizing influenza virus (Flu), cytomegalovirus (CMV), and tumor antigens have been identified (20), but it is likely that T memory stem cells contribute to cellular immune responses against virtually any type of antigen.…”
mentioning
confidence: 99%
“…Several important studies have examined the effects of PTCy and the regeneration of T-cell subset following transplant. 24,85,86 Work is ongoing on other cellular subsets, including natural killer cells. 87 Relapse after transplant continues to be a challenge.…”
Section: Future Directionsmentioning
confidence: 99%